Mengatasi Hambatan Pembelajaran IPS Dengan Metode Belajar Sambil Bermain Di Kelas IV SD Khazanah Ilmu - Taseman taseman; Ainur Risalah; Nur Fatimatuz Zahro; Arum Nur Aisyah; Della Puspita Sari (PEDIR: Journal of Elementary Education, 2021)
This study aims to overcome obstacles in the fourth grade social studies learning activities of SD Khazanah Ilmu using learning while playing. Through the method of learning while playing, educators and students can be actively involved with each other. Educators act as facilitators or who facilitate ongoing learning so that students get real and authentic social studies learning experiences. Obstacles in social studies learning activities for class IV SD Khazanah Ilmu are in the form of difficulties experienced by educators and students of education in implementing social studies learning activities. Therefore, this learning while playing method is adapted to the social studies learning material. So, the games used vary according to the material to be studied. Games that are adapted to the material will make it easier for students to understand social studies learning material, and there is no one game that can be used for all social studies learning material. In overcoming obstacles, social studies learning activities in Class IV SD Khazanah Ilmu can be done by applying learning while playing methods. Methods of role playing, playing puzzles, monopoly games, and traditional games of crank can be applied to social studies learning activities to replace lecture methods that are less effective but are still frequently used today. Through the application of this method, students can be more motivated to learn, practice communication, cooperation, and be responsible for learning.